Sleep Deprivation Modifies Noise-Induced Cochlear Injury Related to the Stress Hormone and Autophagy in Female Mice - Li, Pengjun; Bing, Dan; Wang, Sumei; Chen, Jin; Du, Zhihui; Sun, Yanbo; Qi, Fan; Zhang, Yingmiao; Chu, Hanqi (Frontiers in Neuroscience, 2019)
A lack of sleep is linked with a range of inner ear diseases, including hearing loss and tinnitus. Here, we used a mouse model to investigate the effects of sleep deprivation (SD) on noise vulnerability, and explored the mechanisms that might be involved in vitro, focusing particularly corticosterone levels and autophagic flux in cells. Female BALB/c mice were divided into six groups (control, acoustic trauma [AT]-alone, 1 day [d] SD-alone, 1d SD pre-AT, 5d SD-alone, and 5d SD pre-AT). Cochlear damage was then assessed by analyzing auditory brainstem response (ABR), and by counting outer hair cells (OHCs) and the synaptic ribbons of inner hair cells (IHCs). In addition, we measured levels of serum corticosterone and autophagy protein expression in the basilar membranes by ELISA kits, and western blotting, respectively. We found that SD-alone temporarily elevated ABR wave I amplitude, but had no permanent effect on hearing level or IHC ribbon numbers. Combined with AT, the number of synaptic ribbons in the 1d SD pre-AT group was significantly higher than that in the AT-alone group, whereas the 5d SD pre-AT group showed more severe synaptopathy, and a greater loss of OHCs after 2 weeks than the other experimental groups exposed to noise. Correspondingly, the levels of corticosterone in the AT-alone group were higher than those of the 1d SD pre-AT group, but lower than those of the 5d SD pre-AT group. The 1d SD pre-AT group showed a marked elevation in the expression of microtubule-associated protein 1 light chain 3B (LC3B), whereas the AT-alone group exhibited only a mild increase. In contrast, the levels of LC3B did not change in the 5d SD pre-AT group. Experiments with HEI-OC-1 cells and cochlear basilar membrane cultures showed that high-concentrations of dexamethasone, and the inhibition of autophagy, aggravated cellular apoptosis induced by oxidative stress. In conclusion, noise-induced synaptopathy and hair cell loss can be mitigated by preceding 1d SD, but will be aggravated by preceding 5d SD. These findings may be attributable to corticosterone levels and the extent of autophagy.